Molecular Dynamics Simulations Reveal Mechanistic Insights into Aptamer-induced Structural Rearrangements in Viral Capsid Proteins - Chen Fei Low; Norazli Ghadin; Muhamad Arif Mohamad Jamali (Springer Nature, 2025)
Indexed by WOS/Scopus/ERA